Leukocyte telomere length decreased the risk of mortality in patients with alcohol-associated liver disease - Yi, Jiahong; Guo, Hui; Jiang, Chang; Duan, Junyi; Xue, Ju; Zhao, Yue; He, Wenzhuo; Xia, Liangping (Frontiers in Endocrinology, 2024)
It is necessary to find latent indicators to predict the survival of alcohol-associated liver disease (ALD) patients. Leukocyte telomere length (LTL) was regarded as an indicator of prognosis in several diseases. However, the relationships between LTL and survival as well as cause-specific mortality in ALD patients were still unknown.This study aimed at exploring the underlying link between LTL and the risk of mortality in patients with ALD.The LTL and survival data were gathered from the National Health and Nutrition Examination Survey (NHANES) 1999-2002. The connection between LTL and mortality was assessed by cox regression models and stratified analyses. The non-linear relationship was explored by restricted cubic spline (RCS) analysis. Sensitivity analyses were used to evaluate the robustness of our findings. LTL was a negative factor for all-cause mortality (all p value< 0.05). The risk of cardiovascular disease (CVD) related death was decreased in Q3 (p < 0.001) and Q4 levels of LTL (p < 0.001) compared with Q1 group. Shorter LTL resulted in higher cancer-caused mortality (p = 0.03) in Q2 group. Longer LTL improved survival especially for elder patients (p for trend < 0.001) or males (p for trend = 0.001). Besides, there were L-shaped connections between LTL with all-cause mortality (p for non-linearity = 0.02), as well as cancer-related mortality (p for non-linearity < 0.001). Four sensitivity analyses proved the robustness of our findings.Our research found longer LTL improved survival in patients with ALD and decreased CVD and cancer related mortality. LTL decreased all-cause mortality especially for patients older than 65 years or males. LTL might be a useful biomarker for prognosis among patients with ALD. More prospective studies were needed to assess the relevance between LTL and mortality and explore the underlying mechanisms between them.